The burden of influenza A and B in Mexico from the year 2010 to 2013: An observational, retrospective, database study, on records from the Directorate General of Epidemiology database - Ricardo Cortes-Alcala; Gaël Dos Santos; Rodrigo DeAntonio; Raghavendra Devadiga; Cuitlahuac Ruiz-Matus; Maria E. Jimenez-Corona; Jose A. Diaz-Quinonez; Luis Romano-Mazzotti; Maria Yolanda Cervantes-Apolinar; Pablo Kuri-Morales (Human Vaccines & Immunotherapeutics, 2018)
Despite vaccination programs, influenza still represents a significant disease burden in Mexico. We conducted an observational, retrospective analysis to better understand the epidemiological situation of the influenza virus in Mexico. Analysis of the seasonal patterns of influenza A and B were based on the Directorate General of Epidemiology dataset of influenza-like illness(ILI), and severe acute respiratory infection(SARI) that were recorded between January 2010 and December 2013. Our objectives were 1) to describe influenza A and B activity, by age group, and subtype and, 2) to analyze the number of laboratory-confirmed cases presenting with ILI by influenza type, the regional distribution of influenza, and its clinical features. Three periods of influenza activity were captured: August 2010–January 2011, December 2011–March 2012, and October 2012–March 2013. Cases were reported throughout Mexico, with 50.3% (n = 10,320) of cases found in 18–49 year olds. Over the entire capture period, a total of 76,085 ILI/SARI episodes had swab samples analyzed for influenza, 27% were positive. During the same period, influenza A cases were higher in the 18–49 years old, and influenza B cases in both 5–17 and 18–49 age groups. Peak activity occurred in January 2012 (n = 4,159) and December 2012 (n = 348) for influenza A and B respectively. This analysis confirms that influenza is an important respiratory pathogen for children and adults in Mexico despite vaccination recommendations. School-age children and adolescents were more prone to influenza B infection; while younger adults were susceptible to both influenza A and B viruses. Over the seasons, influenza A and B co-circulated.